Method for improving intergrowth strength of basic pellet hematite complex iron ore fines
By preparing auxiliary raw materials and controlling the proportion of ingredients, the problem of reduced strength of pellets was solved by mixing steel slag, sintered return ore and iron oxide scale with hematite complex iron ore powder, limestone powder and bentonite. This improved the crystallization strength of alkaline pellets and ensured the stability of blast furnace conditions.
Patent Information
- Application Number
- CN202611060770.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-11-03
AI Technical Summary
The strength of the pellets is reduced due to the influence of complex iron ore powder, which affects the stable operation of the blast furnace when it is used in large proportion.
By preparing auxiliary raw materials and controlling the proportion of ingredients, the intercrystallization strength of alkaline pellets is improved by mixing steel slag, sintered return ore and iron oxide scale with hematite complex iron ore powder, limestone powder and bentonite, followed by pelletizing and roasting.
It improved the physical properties of the pellets, reduced powder production, and ensured the stable operation of the blast furnace.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of mineral processing technology, and in particular relates to a method for improving the crystallization strength of alkaline pellet hematoxylin complex iron ore powder. Background Technology
[0002] When using a chain grate-rotary kiln production process, finely ground limestone powder as flux, and hematoxylin and argillaceous complex iron ore powder as iron feedstock to produce basic pellets, the reducibility of the pellets is improved, which is beneficial for blast furnace smelting. However, under the influence of hematoxylin and argillaceous complex iron ore powder, the strength of the pellets decreases, and a large proportion of its use in the blast furnace affects the stable operation of the furnace. Therefore, it is necessary to take measures to improve the intercalation strength of the basic pellets and hematoxylin and argillaceous complex iron ore, improve the physical properties of the pellets, and stabilize the furnace conditions. Summary of the Invention
[0003] The purpose of this invention is to provide a method for improving the crystallization strength of alkaline pellets made from hematoxylin and argillaceous complex iron ore powder, thereby solving the problem that the strength of pellets decreases under the influence of hematoxylin and argillaceous complex iron ore powder, and that the large proportion of powder used in blast furnaces affects the stable operation of the furnace.
[0004] To achieve the above objectives, the present invention adopts the following technical solution: A method for improving the intercalation strength of alkaline pellet hematoxylin complex iron ore powder, the specific steps of which are as follows: S1: Preparation of auxiliary materials Weigh and batch the steel slag, sintered return ore, and iron oxide scale. The specific proportions are: 44-46 parts steel slag, 39-41 parts sintered return ore, and 14-16 parts iron oxide scale. Mix and grind the above auxiliary materials in a ball mill. The proportion of auxiliary materials with a particle size of less than 0.044 mm is more than 80%.
[0005] S2: Ingredients The auxiliary raw materials, limestone powder, hematite powder, and bentonite are mixed and proportioned according to the following weight percentages: 8-88 parts of auxiliary raw materials, 10-50 parts of limestone powder, 892-932 parts of hematite powder, and 9-11 parts of bentonite.
[0006] S3: Ball Making The above mixture is mixed evenly by a high-pressure mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 8-10% (by weight percentage) and a particle size of 8mm-16mm.
[0007] S4: Roasting The material is fed and roasted on a chain grate-rotary kiln at a temperature of 1150-1250℃ to obtain finished pellets with a binary basicity (CaO / SiO2) of 0.6-0.8.
[0008] S5: Cooling After cooling, the high-temperature roasted pellets have a crystallization strength of 1895-2041 N for complex hematologic ore powder.
[0009] The main chemical composition of the steel slag in step S1 is TFe: 24-28%, FeO: 15-20%, CaO: 44-50%, SiO2: 12-15%, MgO: 3-4%. Sintered return ore is the recycled material generated during the sintering process: TFe: 52-55%, FeO: 8-10%, SiO2: 6-8%, Al2O3: 1.6-1.9%, CaO: 9-11%, MgO: 2.7-2.9%. Iron oxide scale is the oxide formed during the steel rolling process: TFe: 67-74%, FeO: 35-65%, SiO2: 0.5-4.0%, Al2O3: 0.3-1.2%.
[0010] In step S1, the steel slag is self-produced converter slag, with the main chemical composition being TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, SiO2: 12.5%, MgO: 3.4%. The sintering return ore is recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%. The iron oxide scale is an oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%.
[0011] In step S2, the content of hematoxylin complex iron ore powder with a particle size less than 0.044 mm is 90-96%, the iron grade of the hematoxylin complex iron ore powder is 64-66%, the FeO content is 15-16%, the SiO2 content is 4-4.5%, the CaO content is 0.4-0.5%, the moisture content is 10-11%, and the bentonite is conventional bentonite purchased from the market, with 83-86% of the particles smaller than 0.074 mm.
[0012] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: By preparing auxiliary raw materials and rationally controlling the proportion of ingredients, the crystallization strength of alkaline hematoxylin and argillaceous complex iron ore powder can be improved, thereby enhancing the physical properties of the pellets. Under the same conditions of falling and colliding in the furnace, the amount of powder generated can be reduced, thus achieving stable furnace conditions. Detailed Implementation
[0013] The technical solution of the present invention will be described in detail below with reference to the embodiments.
[0014] This invention provides a method for improving the crystallization strength of alkaline pelletized hematoxylin complex iron ore powder, the specific steps of which are as follows: Example 1
[0015] S1: Preparation of auxiliary materials: The steel slag, sintered return ore, and iron oxide scale were weighed and batched in the following proportions: 45 parts steel slag, 40 parts sintered return ore, and 15 parts iron oxide scale. The steel slag is converter slag produced by Taiyuan Iron & Steel Group, and its main chemical composition is TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, and SiO2: 12%. 5%, MgO: 3.4%, sintering return ore is the recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%, iron oxide scale is the oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%. The above auxiliary raw materials are mixed and ground in a ball mill to obtain a flux clinker with a proportion of particles smaller than 0.044mm of more than 70%.
[0016] S2: Ingredients: The auxiliary raw materials, hematite powder, and bentonite are mixed and proportioned according to the following weight percentages: auxiliary raw materials: 8 parts, limestone powder: 50 parts, hematite powder: 932 parts, and bentonite: 10 parts. The hematite powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm of 99.5%, an iron grade of 65.8%, an FeO content of 15.3%, a SiO2 content of 4.2%, a CaO content of 0.48%, and a moisture content of 10.7%. The bentonite is commercially available conventional bentonite with a particle size of less than 0.074 mm of 86%.
[0017] S3: Ball Making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 9.6% (by weight) and a particle size of 9mm-15mm.
[0018] S4: Roasting The material is fed and roasted on a chain grate rotary kiln at a temperature of 1200℃ to obtain finished pellets with the following composition: TFe: 63.38%, SiO2: 4.74%, CaO: 3.30%, MgO: 0.85%, Al2O3: 1.03%, and a binary basicity (CaO / SiO2) of 0.7.
[0019] S5: Cooling After the roasted high-temperature pellets were cooled, the intercrystallization strength of the hematoxylin complex iron ore powder was 1895 N. Example 2
[0020] S1: Preparation of auxiliary materials: The steel slag, sintered return ore, and iron oxide scale were weighed and batched in the following proportions: 45 parts steel slag, 40 parts sintered return ore, and 15 parts iron oxide scale. The steel slag is converter slag produced by Taiyuan Iron & Steel Group, and its main chemical composition is TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, and SiO2: 12%. 5%, MgO: 3.4%, sintering return ore is the recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%, iron oxide scale is the oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%. The above auxiliary raw materials are mixed and ground in a ball mill to obtain a flux clinker with a proportion of particles smaller than 0.044mm of more than 70%.
[0021] S2: Ingredients: The auxiliary raw materials, hematite powder, and bentonite are mixed and proportioned according to the following weight percentages: Auxiliary raw materials: 28 parts, limestone powder: 40 parts, hematite powder: 922 parts, and bentonite: 10 parts. The hematite powder is from Lanxian County, Shanxi Province, with a particle size of 99.5% smaller than 0.044 mm, an iron grade of 65.8%, an FeO content of 15.3%, a SiO2 content of 4.2%, a CaO content of 0.48%, and a moisture content of 10.7%. The bentonite is commercially available conventional bentonite, with 86% of the particles smaller than 0.074 mm.
[0022] S3: Ball Making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 9.4% (by weight) and a particle size of 9mm-15mm.
[0023] S4: Roasting The material is fed and roasted on a chain grate rotary kiln at a temperature of 1180℃ to obtain finished ore pellets with the following composition: TFe: 63.38%, SiO2: 4.74%, CaO: 3.30%, MgO: 0.85%, Al2O3: 1.03%, and a binary basicity (CaO / SiO2) of 0.7.
[0024] S5: Cooling After cooling, the high-temperature roasted pellets have a crystallization strength of 1935 N for the hematologic complex iron ore powder. Example 3
[0025] S1: Preparation of auxiliary materials: The steel slag, sintered return ore, and iron oxide scale were weighed and batched in the following proportions: 45 parts steel slag, 40 parts sintered return ore, and 15 parts iron oxide scale. The steel slag is converter slag produced by Taiyuan Iron & Steel Group, and its main chemical composition is TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, and SiO2: 12%. 5%, MgO: 3.4%, sintering return ore is the recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%, iron oxide scale is the oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%. The above auxiliary raw materials are mixed and ground in a ball mill to obtain a flux clinker with a proportion of particles smaller than 0.044mm of more than 70%.
[0026] S2: Ingredients: The auxiliary raw materials, hematite powder, and bentonite are mixed and proportioned according to the following weight percentages: Auxiliary raw materials: 48 parts, limestone powder: 30 parts, hematite powder: 912 parts, and bentonite: 10 parts. The hematite powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm of 99.5%, an iron grade of 65.8%, an FeO content of 15.3%, a SiO2 content of 4.2%, a CaO content of 0.48%, and a moisture content of 10.7%. The bentonite is commercially available conventional bentonite with a particle size of less than 0.074 mm of 86%.
[0027] S3: Ball Making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 9.4% (by weight) and a particle size of 9mm-12mm.
[0028] S4: Roasting The material is fed and roasted on a chain grate rotary kiln at a temperature of 1180℃ to obtain finished ore pellets with the following composition: TFe: 63.38%, SiO2: 4.74%, CaO: 3.30%, MgO: 0.85%, Al2O3: 1.03%, and a binary basicity (CaO / SiO2) of 0.7.
[0029] S5: Cooling After the roasted high-temperature pellets were cooled, the intercrystallization strength of the hematoxylin complex iron ore powder was 1980 N. Example 4
[0030] S1: Preparation of auxiliary materials: The steel slag, sintered return ore, and iron oxide scale were weighed and batched in the following proportions: 45 parts steel slag, 40 parts sintered return ore, and 15 parts iron oxide scale. The steel slag is converter slag produced by Taiyuan Iron & Steel Group, and its main chemical composition is TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, and SiO2: 12%. 5%, MgO: 3.4%, sintered return ore is the recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%, iron oxide scale is the oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%. The above auxiliary raw materials are mixed and ground in a ball mill to obtain a flux clinker with a proportion of more than 70% smaller than 0.044mm. The above raw materials are mixed and ground in a ball mill to obtain an auxiliary raw material (hereinafter referred to as "flux clinker") with a proportion of more than 70% smaller than 0.044mm.
[0031] S2: Ingredients: The auxiliary raw materials, hematite powder, and bentonite are mixed and proportioned according to the following weight percentages: Auxiliary raw materials: 68 parts, limestone powder: 20 parts, hematite powder: 902 parts, and bentonite: 10 parts. The hematite powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm (99.5%), an iron grade of 65.8%, an FeO content of 15.3%, a SiO2 content of 4.2%, a CaO content of 0.48%, and a moisture content of 10.7%. The bentonite is commercially available, with 86% of the particles smaller than 0.074 mm.
[0032] S3: Ball Making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 9.2% (by weight) and a particle size of 8mm-10mm.
[0033] S4: Roasting The material is fed and roasted on a chain grate rotary kiln at a temperature of 1180℃ to obtain finished ore pellets with the following composition: TFe: 63.38%, SiO2: 4.74%, CaO: 3.30%, MgO: 0.85%, Al2O3: 1.03%, and a binary basicity (CaO / SiO2) of 0.7.
[0034] S5: Cooling After the roasted high-temperature pellets were cooled, the intercrystallization strength of the hematoxylin complex iron ore powder was 2035 N. Example 5
[0035] S1: Preparation of auxiliary materials: The steel slag, sintered return ore, and iron oxide scale were weighed and batched in the following proportions: 45 parts steel slag, 40 parts sintered return ore, and 15 parts iron oxide scale. The steel slag is converter slag produced by Taiyuan Iron & Steel Group, and its main chemical composition is TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, and SiO2: 12%. 5%, MgO: 3.4%, sintering return ore is the recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%, iron oxide scale is the oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%. The above auxiliary raw materials are mixed and ground in a ball mill to obtain a flux clinker with a proportion of particles smaller than 0.044mm of more than 70%.
[0036] S2: Ingredients: The auxiliary raw materials, hematite powder, and bentonite are mixed and proportioned according to the following weight percentages: auxiliary raw materials: 88 parts, limestone powder: 10 parts, iron ore powder: 892 parts, bentonite: 10 parts. The hematite powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm of 99.5%, an iron grade of 65.8%, an FeO content of 15.3%, a SiO2 content of 4.2%, a CaO content of 0.48%, and a moisture content of 10.7%. The bentonite is commercially available conventional bentonite, with 86% of the particles smaller than 0.074 mm.
[0037] S3: Ball Making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 9.2% (by weight) and a particle size of 8mm-10mm.
[0038] S4: Roasting The material is fed and roasted on a chain grate rotary kiln at a temperature of 1160℃ to obtain finished pellets with the following composition: TFe: 63.38%, SiO2: 4.74%, CaO: 3.30%, MgO: 0.85%, Al2O3: 1.03%, and a binary basicity (CaO / SiO2) of 0.7.
[0039] S5: Cooling After the roasted high-temperature pellets were cooled, the intercrystallization strength of the hematoxylin complex iron ore powder was 2041 N.
[0040] Comparative Example 1 (1) Ingredients Hematite powder, limestone powder, and bentonite are mixed and proportioned according to the following weight percentages: hematite powder: 936 parts, limestone powder: 54 parts, bentonite: 10 parts. The hematite powder is from Lanxian County, Shanxi Province, with 99.5% of particles smaller than 0.044mm, an iron grade of 65.8%, FeO content of 15.3%, SiO2 content of 4.2%, CaO content of 0.48%, and moisture content of 10.7%. The bentonite is commercially available, with 86% of particles smaller than 0.074mm.
[0041] (2) Ball making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 9.8% (by weight) and an average particle size of 8mm-16mm.
[0042] S3: Roasting The material is fed and roasted on a chain grate rotary kiln at a temperature of 1220℃ to obtain finished ore pellets with the following composition: TFe 63.38%, SiO2 4.74%, CaO 3.30%, MgO 0.85%, Al2O3 1.03%, and a binary basicity (CaO / SiO2) of 0.7.
[0043] S4: Cooling After the roasted high-temperature pellets were cooled, the intercrystallization strength of the hematoxylin complex iron ore powder was 1890 N.
[0044] The above comparative examples show that alkaline pellets produced by conventional processes have low intercrystallization strength of hematologic complex iron ore powder.
[0045] Comparison of the above embodiments with comparative examples: In Example 1 of this invention, a mixture of 8 parts finely ground steel slag, sintered return ore, and iron oxide scale was added to hematite complex iron ore powder. The mixture was then batched, pelletized, roasted, and cooled to obtain finished pellets. The green pellets had a moisture content of 9.6%, a particle size of 9mm-15mm, a roasting temperature of 1200℃, and a crystal strength of 1895N, which is 5N higher than that of Comparative Example 1.
[0046] In Example 2 of this invention, 28 parts of a mixture of finely ground steel slag, sintered return ore, and iron oxide scale were added to the hematite complex iron ore powder. The mixture was then batched, pelletized, roasted, and cooled to obtain finished pellets. The green pellets had a moisture content of 9.4%, a particle size of 9 mm-15 mm, a roasting temperature of 1180 °C, and a crystal strength of 1935 N, which is 45 N higher than that of Comparative Example 1.
[0047] In Example 3 of this invention, 48 parts of a mixture of finely ground steel slag, sintered return ore, and iron oxide scale were added to hematoxylin and argillaceous complex iron ore powder. The mixture was then batched, pelletized, roasted, and cooled to obtain finished pellets. The green pellets had a moisture content of 9.4%, a particle size of 9mm-12mm, a roasting temperature of 1180℃, and a crystallization strength of 1980N, which is 100N higher than that of Comparative Example 1.
[0048] In Example 4 of this invention, 68 parts of a mixture of finely ground steel slag, sintered return ore, and iron oxide scale were added to hematoxylin and argillaceous complex iron ore powder. The mixture was then batched, pelletized, roasted, and cooled to obtain finished pellets. The green pellets had a moisture content of 9.2%, a particle size of 8-10 mm, a roasting temperature of 1180℃, and a crystal strength of 2035 N, which is 145 N higher than that of Comparative Example 1.
[0049] In Example 5 of this invention, 88 parts of a mixture of finely ground steel slag, sintered return ore, and iron oxide scale were added to hematite complex iron ore powder. The mixture was then batched, pelletized, roasted, and cooled to obtain finished pellets. The green pellets had a moisture content of 9.2%, a particle size of 8-10 mm, a roasting temperature of 1160°C, and a crystal strength of 2041 N, which is 151 N higher than Comparative Example 1, but not significantly higher than Example 4.
Claims
1. A method for improving the intercalation strength of alkaline pellet hematoxylin complex iron ore powder, characterized in that, The specific steps are as follows: S1: Preparation of auxiliary materials Weigh and batch the steel slag, sintered return ore, and iron oxide scale. The specific proportions are: 44-46 parts steel slag, 39-41 parts sintered return ore, and 14-16 parts iron oxide scale. Mix and grind the above auxiliary materials in a ball mill. The proportion of auxiliary materials with a particle size of less than 0.044 mm is more than 80%. S2: Ingredients The auxiliary raw materials, limestone powder, iron ore powder, and bentonite are mixed and proportioned according to the following weight percentages: 8-88 parts of auxiliary raw materials, 10-50 parts of limestone powder, 892-932 parts of iron ore powder, and 9-11 parts of bentonite. S3: Ball Making The above mixture is mixed evenly by a high-power mixer, and then added to a disc pelletizer to replenish moisture and produce pellets with a moisture content of 8-10% (by weight percentage) and a particle size of 8mm-16mm. S4: Roasting The material is fed and roasted on a chain grate-rotary kiln at a temperature of 1150-1250℃ to obtain finished pellets with a binary basicity (CaO / SiO2) of 0.6-0.
8. S5: Cooling After cooling, the high-temperature roasted pellets have a crystallization strength of 1895-2041 N for complex hematologic ore powder.
2. The method for improving the intercalation strength of alkaline pellet hematoxylin complex iron ore powder according to claim 1, characterized in that, The main chemical composition of the steel slag in step S1 is TFe: 24-28%, FeO: 15-20%, CaO: 44-50%, SiO2: 12-15%, MgO: 3-4%. Sintered return ore is the recycled material generated during the sintering process: TFe: 52-55%, FeO: 8-10%, SiO2: 6-8%, Al2O3: 1.6-1.9%, CaO: 9-11%, MgO: 2.7-2.9%. Iron oxide scale is the oxide formed during the steel rolling process: TFe: 67-74%, FeO: 35-65%, SiO2: 0.5-4.0%, Al2O3: 0.3-1.2%.
3. The method for improving the intercalation strength of alkaline pellet hematoxylin complex iron ore powder according to claim 2, characterized in that, In step S1, the steel slag is self-produced converter slag, with the main chemical composition being TFe: 26.3%, FeO: 17.1%, CaO: 47.5%, SiO2: 12.5%, MgO: 3.4%. The sintering return ore is recycled material generated during the sintering production process: TFe: 53.5%, FeO: 8.1%, SiO2: 6.9%, Al2O3: 1.7%, CaO: 10.1%, MgO: 2.7%. The iron oxide scale is an oxide formed during the steel rolling process: TFe: 70.4%, FeO: 60.5%, SiO2: 0.9%, Al2O3: 0.7%.
4. The method for improving the intercalation strength of alkaline pellet hematoxylin complex iron ore powder according to claim 1, characterized in that, In step S2, the content of iron ore powder with a particle size less than 0.044mm is 90-96%, the iron grade of iron ore powder is 64-66%, the FeO content is 15-16%, the SiO2 content is 4-4.5%, the CaO content is 0.4-0.5%, the moisture content is 10-11%, and the bentonite is commercially available conventional bentonite with a proportion of particles smaller than 0.074mm of 83-86%.
